(untitled) (The Conference Hub, 2025)
Between 1937 and 1938, over 172,000 ethnic Koreans were deported from the Soviet Far East to Central Asia under NKVD Resolution No. 1428–326ss, justified as a measure “to suppress Japanese espionage in the Far Eastern territories” [1, p.2]. However, historians such as Gelb (1995) emphasize that the deportation was part of Stalin’s broader ethnic engineering project rather than a genuine security concern [2, p.36–38]. The deported population included even remote communities from Okhotsk and Magadan, far beyond any military relevance [1, p.2; 2, p.40].